Combining Coherent Hard X-Ray Tomographies with Phase Retrieval to Generate Three-Dimensional Models of Forming Bone - Bortel, Emely L.; Langer, Max; Rack, Alexander; Forien, Jean-Baptiste; Duda, Georg N.; Fratzl, Peter; Zaslansky, Paul (Frontiers in Materials, 2017)
Holotomography, a phase sensitive synchrotron-based μCT modality, is a quantitative 3D imaging method. By exploiting partial spatial X-ray coherence, bones can be imaged volumetrically with high resolution coupled with impressive density sensitivity. This tomographic method reveals the main characteristics of the important tissue compartments in forming bones, including the rapidly-changing soft tissue and the partially or fully mineralized bone regions, while revealing subtle density differences in 3D. Here we show typical results observed within the growing femur bone midshafts of healthy mice that are 1, 3, 7, 10 and 14 days old (postpartum). Our results make use of partially-coherent synchrotron radiation employing inline Fresnel-propagation in multiple tomographic datasets obtained in the imaging beamline ID19 of the ESRF. The exquisite detail creates maps of the juxtaposed soft, partially mineralized and highly mineralized bone revealing the environment in which bone cells create and shape the matrix. This high resolution 3D data is a step towards creating realistic computational models that may be used to study the dynamic processes involved in bone tissue formation and adaptation. Such data will enhance our understanding of the important biomechanical interactions directing maturation and shaping of the bone micro- and macro-geometries.